Вакуумний захоплювач (Патент на корисну модель № 80288) - Якимчук, Микола Володимирович; Іванова, Людмила Іллівна (My University, 2013)
Вакуумний захоплювач для захоплюючих пристроїв містить корпус, привідний корпус, вакуумний блок. Корпус захоплювача виконано у вигляді пустотілого циліндра, в верхній частині якого є патрубок, дно має множину отворів у вигляді конусів, нижня частина яких має форму шестигранника, а верхня частина виконана у вигляді кола. Vacuum gripping devices for exciting comprises a housing , a drive enclosure, vacuum unit . Housing Occupants designed as hollow cylinder, the top of which is a pipe , the bottom has a plurality of apertures in the form of cones , the lower part of which is shaped hexagon, and the upper part is made in the form of gripping kola.Vakuumnyy for exciting devices comprising a housing , a drive enclosure , vacuum block. Housing Occupants designed as hollow cylinder, the top of which is a pipe , the bottom has a plurality of apertures in the form of cones , the lower part of which is shaped hexagon, and the upper part is designed as a circle.
Keywords: вакуумний захват; пустотілий циліндр; vacuum gripper; hollow cylinder; кафедра теоретичної механіки та ресурсоощадних технологій; кафедра мехатроніки та пакувальної техніки